Bran Hambric : the Farfield curse - Nation, Kaleb (Naperville, Ill. : Jabberwocky, 2009)
Very strange occurrences have long surrounded fourteen-year-old Bran, who learns of his link to a curse created by his murdered mother and strives to make things right, hindered by the ban on magic in the city of Dunce and pursued by his mother's former masters.
Keywords: Magic -- Juvenile fiction; Foster home care -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Fantasy; Youths' writings